2008
DOI: 10.1111/j.1532-950x.2008.00441.x
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Biomechanical Comparison of the 2.4 mm UniLOCK® Reconstruction Plate Using 2.4 mm Locking Versus Standard Screws for Fixation of Acetabular Osteotomy in Dogs

Abstract: There is no apparent advantage of locking plate fixation over standard plate fixation of 2-piece ex vivo acetabular fractures using the 2.4 mm uniLOCK reconstruction plate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
21

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(51 citation statements)
references
References 31 publications
0
28
0
21
Order By: Relevance
“…1,5,9,[11][12][13][14][15][16][17][18][19] Biomechanical in vitro evaluation of different types fixation methods has been previously published, 17,20,21 including one study which compared use of locking versus non-locking plate and screw constructs. 22 Increasing implant construct stiffness by use of techniques such as plate luting has been suggested to reduce strain at the fracture site and to decrease the risk for implant failure. 17,23,24 It has been reported that implant shift may occur during screw tightening with reconstruction plates, 17 and similarly that loss of reduction during plate fixation using veterinary acetabular non-locking plates may occur.…”
Section: Introductionmentioning
confidence: 99%
“…1,5,9,[11][12][13][14][15][16][17][18][19] Biomechanical in vitro evaluation of different types fixation methods has been previously published, 17,20,21 including one study which compared use of locking versus non-locking plate and screw constructs. 22 Increasing implant construct stiffness by use of techniques such as plate luting has been suggested to reduce strain at the fracture site and to decrease the risk for implant failure. 17,23,24 It has been reported that implant shift may occur during screw tightening with reconstruction plates, 17 and similarly that loss of reduction during plate fixation using veterinary acetabular non-locking plates may occur.…”
Section: Introductionmentioning
confidence: 99%
“…Locking compression plates (LCP) are used for fracture fixation in dogs, particularly for comminuted long bone fractures . The LCP provides a more rigid and biomechanically stable fixation compared to conventional plating methods using the dynamic compression plates (DCP) with nonlocking screws . The LCP contains combination holes, which allow for the insertion of either a locking or nonlocking screw, thereby combining the advantages of interfragmentary compression, a feature of DCP, with the stability of a fixed‐angle construct that mimics the biomechanics of an external fixator …”
mentioning
confidence: 99%
“…1,2 The LCP provides a more rigid and biomechanically stable fixation compared to conventional plating methods using the dynamic compression plates (DCP) with nonlocking screws. [3][4][5][6][7][8][9][10] The LCP contains combination holes, which allow for the insertion of either a locking or nonlocking screw, thereby combining the advantages of interfragmentary compression, a feature of DCP, with the stability of a fixedangle construct that mimics the biomechanics of an external fixator. 9,11,12 In practice, a hybrid construct may be created with locking and nonlocking screws in an LCP, despite concerns for incompatible biomechanical properties.…”
mentioning
confidence: 99%
“…In small animals, biomechanical evaluation was also performed on acetabular fractures of canine cadavers for the same purpose 23 . However, there are unresolved questions in relation to the influence of screw length on the locking reconstruction plate that were investigated in the present study.…”
Section: Discussionmentioning
confidence: 99%